MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA DALAM PELAJARAN MELALUI KELOMPOK KECIL - Abdurrohman, Abdurrohman (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This journal explain the efforts to improve the activity and learning outcomes of students in lessons through small group methods. This study uses a test method and classroom action observation. Data analysis using descriptive analysis. The research subject was the sixth grade students of Nunggal Sari Elementary School. In this study it was found: (1) the activity of students in participating in PAI learning before the action was held in the high and very high categories was still low, namely 20.8% or 5 people. (2) Increasing the activeness of students after being given action through small groups, namely TO = 20.8%, T1 = 54.2%, T2 = 62.5%, and T3 = 95.8%. (3) Student learning outcomes before action is 33, 3% or 8 students. (4) Improving student learning outcomes after being given actions through small groups, namely To = 33.3%, T1 = 58.4%, T2 = 79.2%, and T3 = 91.7%. Thus, it has been proven that learning small group methods can increase student activity and learning outcomes.